Exploring the potential of ultrasound combined with sucrose treatments for germination and growth of sunflower sprouts - Liu, Zifei (2024)
Ultrasound is a promising physical method for enhancing the germination of leguminous plants, while sucrose supplementation can boost plant growth and metabolism. However, limited studies have explored the synergistic effects and metabolic mechanisms of ultrasound and sucrose on sunflower sprouts. This study comprehensively investigated the impacts of ultrasound, sucrose, and their combination (US-Suc) on the germination and seedling growth of sunflower seeds. Overall, the combine treatment significantly increased the germination rate, length and weight of sunflower sprouts, compared to either individual treatment. Scanning electron microscope images showed that the US-Suc combination induced a distinct microstructural alteration, enhancing the water absorption capacity of sunflower seeds. Additionally, sunflower seeds exhibited increased activity of endogenous enzymes with antioxidant properties following US-Suc treatment. Lastly, Nuclear magnetic resonance-based metabolomics analysis demonstrated that the US-Suc treatment had a distinct regulatory impact on the metabolic profile compared to either treatment alone. The metabolism of carbohydrates and phenolic compounds was significantly up-regulated upon US-Suc treatment, leading to improved plant growth and resistance to environmental stress. In conclusion, pre-treating with ultrasound in combination with external sucrose application showed great promise in seed germination, enhancing nutrient accumulation in sunflower sprouts by accelerating water uptake and boosting enzyme activity. Thus, US-Suc represents an effective approach to increase both yield and nutritional value of sunflower sprouts.